“A thrilling beauty”?: Violence, Transcendence and the Shankill Butchers in Eoin McNamee’s Resurrection Man - Billy Gray (Estudios Irlandeses, 2014)
The Shankill Butchers, a small group of UVF members based in the Shankill Road during the 1970s, acquired a reputation for indulging in pathological violence to a degree hitherto unparalleled in the annals of “Troubles”-related murders. Eoin McNamee’s Resurrection Man has been accorded a great degree of critical attention regarding the contentious manner in which it has attempted to investigate the Shankill Butchers’ legacy. My article attempts to suggest that the novel’s metafictive universe and innovative generic hybridity represent an attempt to transcend the spatial borders of Northern Ireland in order to present the conflict as an allegory of existential, postmodern alienation. The violent psychopathology of the Shankill Butchers is, in McNamee’s text, of universal as opposed to local significance, and violence is controversially portrayed as a search for intimacy and transcendence in a world defined by virtual reality.